Discursive Practices in Chinese Talk Shows_Semi-institutional Communication Shaped by Multi-dimensional Power Relations - Yang, Chen (Advances in Social Sciences Research Journal, 2021)
Similar to American talk shows, the institutional communication of Chinese talk shows is also affected by complicated and mutually influencing power relations. Therefore, through the analysis of discourse practice and power relations, the author hopes to reveal some unique characteristics of the institutional communication of talk shows in mainland China. By utilizing Sinclair and Coulthard’s rank scale model, an episode of A Date with Lu Yu was selected for a case study of discursive communication. The study shows that Chinese talk shows shared the common characteristics of semi-institutional communication with western counterpart. Besides, the hierarchical structure of communication is prominently reflected in Chinese talk shows. The social power relations between hosts, guests and external forces shape the discourse structure of Chinese talk shows. In particular, commercial organizations that sponsor media have great power in determining the goals and shaping the forms of discourse practice.